Fitness running - Brown, Richard L. 1937- (Human Kinetics, 2015)
Whether running for health, competitively, or both, this book includes established programmes to help runners achieve their goals. It also contains specific recommendations for female runners and information on gear and gadgets, cross-training, stretching and recovery. Each workout is prioritised according to individual goals.